Adverse pregnancy outcomes and long term risk of ischemic heart disease in mothers: national cohort and co-sibling study. (1st February 2023) - Crump, Casey; Sundquist, Jan; McLaughlin, Mary Ann; Dolan, Siobhan M; Govindarajulu, Usha; Sieh, Weiva; Sundquist, Kristina
Abstract: Objective: To examine the associations between five major adverse pregnancy outcomes and long term risks of ischemic heart disease in mothers. Design: National cohort study. Setting: Sweden. Participants: All 2 195 266 women with a first singleton delivery in Sweden during 1973-2015. Main outcome measures: The main outcome measure was incidence of ischemic heart disease from delivery to 2018, identified from nationwide inpatient and outpatient diagnoses. Cox regression was used to calculate hazard ratios for ischemic heart disease associated with preterm delivery, small for gestational age, pre-eclampsia, other hypertensive disorders of pregnancy, and gestational diabetes, adjusting for other adverse pregnancy outcomes and maternal factors. Co-sibling analyses assessed for confounding by shared familial (genetic and environmental) factors. Results: During 53.6 million person years of follow-up, ischemic heart disease was diagnosed in 83 881 (3.8%) women. All five adverse pregnancy outcomes were independently associated with increased risk of ischemic heart disease. In the 10 years after delivery, adjusted hazard ratios for ischemic heart disease associated with specific adverse pregnancy outcomes were 2.09 (95% confidence interval 1.77 to 2.46) for other hypertensive disorders of pregnancy, 1.72 (1.55 to 1.90) for preterm delivery, 1.54 (1.37 to 1.72) for pre-eclampsia, 1.30 (1.09 to 1.56) for gestational diabetes, and 1.10 (1.00 to 1.21) for small for gestational age. The hazard ratios remained significantly increased even 30-46 years after delivery: 1.47 (1.30 to 1.66) for other hypertensive disorders of pregnancy, 1.40 (1.29 to 1.51) for gestational diabetes, 1.32 (1.28 to 1.36) for pre-eclampsia, 1.23 (1.19 to 1.27) for preterm delivery, and 1.16 (1.13 to 1.19) for small for gestational age. These findings were only partially (<45%) explained by shared familial (genetic or environmental) factors. Women who experienced multiple adverse pregnancy outcomes showed further increases in risk (eg, <10 years after delivery, adjusted hazard ratios associated with 1, 2, or ≥3 adverse pregnancy outcomes were 1.29 (1.19 to 1.39), 1.80 (1.59 to 2.03), and 2.26 (1.89 to 2.70), respectively)). Conclusions: In this large national cohort, women who experienced any of five major adverse pregnancy outcomes showed an increased risk for ischemic heart disease up to 46 years after delivery. Women with adverse pregnancy outcomes should be considered for early preventive evaluation and long term risk reduction to help prevent the development of ischemic heart disease.